2014
DOI: 10.1002/pssc.201300524
|View full text |Cite
|
Sign up to set email alerts
|

AlN/AlGaN/GaN buffer optimization on silicon (111): bow and crystal quality control for Si‐CMOS fabs

Abstract: In GaN‐on‐silicon there are many challenges which are currently encountered when making this technology compatible with standard Si‐CMOS fabs especially the bow. Bringing this technology to CMOS fabs can potentially drive the costs down, in addition to the cost advantage expected from large wafer sizes. We report here on the impact of AlN nucleation layer on crystal quality and bow. The focus will be on V/III ratios and pre‐dose conditions for AlN, which have considerable effect on the AlN/AlGaN/GaN buffer str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The Al content of the AlGaN buffer layer showed no correlation with the VDBV of the HEMT structure on the AlN/Si template. Meanwhile, Kandaswamy et al reported that the crystal quality and surface pit of a HEMT structure has a strong dependency on the growth conditions of the AlN NL . These results suggest that the variation of the VDBV can be correlated with the growth conditions under which surface pits are formed in the AlN NL.…”
Section: Introductionmentioning
confidence: 99%
“…The Al content of the AlGaN buffer layer showed no correlation with the VDBV of the HEMT structure on the AlN/Si template. Meanwhile, Kandaswamy et al reported that the crystal quality and surface pit of a HEMT structure has a strong dependency on the growth conditions of the AlN NL . These results suggest that the variation of the VDBV can be correlated with the growth conditions under which surface pits are formed in the AlN NL.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] It has been shown that the AlN nucleation layer and its interface with a Si substrate plays a key role in formation of defects in the overgrown epitaxial structure, such as melt-back defects, inversion domains, V-pits or hillocks. [6][7][8][9][10] Through the AlN nucleation layer one can control stress and crystal quality in subsequent buffer and GaN layers. [7][8][9][10][11] Careful pre-treatment of Si substrate properties and the nucleation process can improve electrical properties of the HEMT devices such as a reduction of vertical leakage current (VLC).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Through the AlN nucleation layer one can control stress and crystal quality in subsequent buffer and GaN layers. [7][8][9][10][11] Careful pre-treatment of Si substrate properties and the nucleation process can improve electrical properties of the HEMT devices such as a reduction of vertical leakage current (VLC). 9,[12][13][14][15] It has also been recently confirmed that the AlN/Si interface has a significant influence on the overall leakage and charge transport through the entire epitaxial structure during the HEMT operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations